2018
DOI: 10.1016/j.molcel.2018.06.012
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic p53 Mutation Library Links Differential Functional Impact to Cancer Mutation Pattern and Evolutionary Conservation

Abstract: The TP53 gene is frequently mutated in human cancer. Research has focused predominantly on six major "hotspot" codons, which account for only ∼30% of cancer-associated p53 mutations. To comprehensively characterize the consequences of the p53 mutation spectrum, we created a synthetically designed library and measured the functional impact of ∼10,000 DNA-binding domain (DBD) p53 variants in human cells in culture and in vivo. Our results highlight the differential outcome of distinct p53 mutations in human pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(195 citation statements)
references
References 52 publications
7
176
2
Order By: Relevance
“…Therefore, it is recommended that the p53 isoform expression is reported with respect to the mutational status of TP53, to establish more precise correlations with clinical outcomes [109,110]. However, stating whether p53 is WT or mutant may not suffice as it is becoming apparent that the mutational landscape of p53 is highly heterogeneous and the various p53 mutants are not equal in their cellular and phenotypical effects [111,112]. For example, Li Fraumeni syndrome (LFS) patients with specific p53 DBD mutations (associated with impaired anti-proliferative functions in H1299 cultured cells) have tumour incidences at an earlier age compared to LFS patients harbouring germline TP53 mutations retaining anti-proliferative functions [112].…”
Section: Isoforms Studied N Summary Of Key Results Referencesmentioning
confidence: 99%
“…Therefore, it is recommended that the p53 isoform expression is reported with respect to the mutational status of TP53, to establish more precise correlations with clinical outcomes [109,110]. However, stating whether p53 is WT or mutant may not suffice as it is becoming apparent that the mutational landscape of p53 is highly heterogeneous and the various p53 mutants are not equal in their cellular and phenotypical effects [111,112]. For example, Li Fraumeni syndrome (LFS) patients with specific p53 DBD mutations (associated with impaired anti-proliferative functions in H1299 cultured cells) have tumour incidences at an earlier age compared to LFS patients harbouring germline TP53 mutations retaining anti-proliferative functions [112].…”
Section: Isoforms Studied N Summary Of Key Results Referencesmentioning
confidence: 99%
“…Results from systematic transactivation assays performed in yeast (Kato et al, 2003) were used for comparison with the classifica- When compared to data from DBD region variants assayed for antiproliferative function using a high through-put mammalian assay (Kotler et al, 2018) In addition, we compared our results to data from mammalian clonogenic survival assays conducted as part of this study, which also included reduced penetrance p.Arg337His variant as a partial activity pathogenic control. As shown in Figure 4 the performance of the clonogenic assay and systematic transactivation assays (Kato et al, 2003) was moderate, with an R 2 of 0.58.…”
Section: Results From Functional Assays Correlate With Assigned Varmentioning
confidence: 99%
“…Variants classified as pathogenic or likely pathogenic by the model were associated with earlier age of cancer onset (including a greater proportion of pediatric cancers), and were enriched in Classic LFS probands and depleted in a cohort of cancer-free women over 70 years. When compared to the output of reported functional assays, the majority of variants classified as pathogenic or likely pathogenic were nonfunctional in transactivation yeast assays (Kato et al, 2003), showed disruption of antiproliferative function/LOF (Giacomelli et al, 2018;Kotler et al, 2018), or reduced activity in the mammalian clonogenic survival assays developed in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations